Determinants of mobile consumers' perceived value of location-based advertising and user responses - Paragas, Fernando (2017)
This study examines factors affecting mobile consumers' perceived advertising value of latest location-based mobile advertising (LBA) and its relationship with user responses. Data was collected from a nationally representative web survey of 605 respondents who fit the demographic quotas of mobile consumers in Singapore. Partial least squares results show that privacy concerns have a stronger negative effect on perceived LBA value than perceived sacrifice, while perceived utility, utilisation of contextual information and trust positively predict perceived LBA value. Moreover, perceived LBA value increases consumers' responses to purchase advertised brands, followed by searching for brand information and passing LBA to others. Implications for mobile advertising theories and practices are discussed.